G194(P) Delayed diagnosis of Type 1 Diabetes Mellitus (T1DM)in children. (27th April 2016) - Kear, C; Fisher, T; Westwood, E; Sachdev, P; Denvir, L
Abstract : Background: There are around 3000 new paediatric diagnoses of T1DM a year in the UK with around 25% presenting in DKA (Diabetic ketoacidosis). Cerebral oedema remains the most common cause of mortality in DKA, particularly in children and adolescents, and is more likely to occur in newly diagnosed T1DM. Guidelines for the management of suspected T1DM in primary care recommends that patients presenting to the GP with symptoms suggestive of T1DM (polydipsia, polyuria, thirst, lethargy, weight loss) should have an immediate random finger prick capillary glucose test. If positive (>11.1mmol/L), the child should be referred to specialist diabetes services in secondary care the same day. Aim: The aim of this study is to analyse cases of delayed presentation to secondary care in an attempt to ascertain reasons for this delay. The ultimate aim is to increase awareness, amongst primary care professionals, of the guidance surrounding the diagnosis of T1DM and consequently decrease morbidity and mortality in newly diagnosed T1DM. Methods: A retrospective case series analysis of patients presenting with a delayed or missed diagnosis of T1DM between 2012–2015. Results: 12 cases (2 female, age range 1.5–15 years) of delayed presentation of T1DM to hospital were identified over a 3 year span. This number represents 10% of new diagnoses over this period. These patients presented to primary care with core signs and symptoms of T1DM. None had an immediate capillary blood glucose check. 1/12 (8%) had a blood glucose checked but this was sent to the laboratory, this was then not actioned appropriately. The mean delay between presentation to the GP and to hospital was 4.6 days (range 12 h-21 days). 6/12 (50%) of children presented to hospital in DKA. 2 of these children had prolonged stays in intensive care and have significant long-term sequelae. Conclusion: 10% of children presenting with new diagnoses of T1DM have a delayed presentation to hospital. Prompt recognition and referral of children with suspected diabetes is vital to prevent life-threatening DKA. Reasons for delayed presentations include: failure to recognise signs and symptoms of diabetes; failure to perform immediate finger prick blood glucose and failure to take appropriate action when an abnormal result is detected.